Against the Odds: The Potential of Swarm Electrification for Small Island Development States. (December 2016) - Koepke, Mathias; Groh, Sebastian
Abstract: The paper builds on earlier observations using system complexity theory to explain the characteristics of a swarm electrification approach using existing small, distributed renewable energy generation infrastructure integrated into a grid. The concept is based on swarm intelligence where information and electricity flow between neighbors to achieve a compounding network effect, in that they are linked together to form a microgrid but at the same time showing a high degree of resilience as each node/ household can also operate independently. The paper contrasts this approach with traditional stand-alone and minigrid systems in small island development states using the multi-tier framework of measuring energy access and taking into account the particularities that these have, especially with regards to infrastructure and geography. The authors make use of qualitative and quantitative results from first practical applications of swarm electrification in Bangladesh.